Attitudes of prehospital providers on transport decision-making in the management of patients with a suicide attempt refusing care: A survey based on the Mental Health Care Act of 2002 - Katya Evans; Heike Geduld; Willem Stassen (South African Journal of Psychiatry, 2018)
Background: Given the frequency of suicidal patients making attempts prior to a completed suicide, emergency access to mental health care services could lead to significant reduction in morbidity and mortality for these patients.